FISH and calcofluor staining techniques to detect in situ filamentous fungal biofilms in water - Gonçalves, A. B. (2006)
Filamentous fungi are a ubiquitous and diverse group of eukaryotic organisms and may contribute, along with bacteria, yeasts, protozoa and viruses, to the formation of biofilms in water distribution systems. However, fungal involvement in biofilms has not been demonstrated unambiguously. Furthermore, these fungi may be responsible for the production of tastes, odours and mycotoxins in drinking water making their early detection important. To overcome these problems a combination of two fluorescent techniques for direct detection was tested: (a) Fluorescence In Situ Hybridization (FISH) employing the universal rRNA probe EUK516, labelled with the red Cy3, and (b) staining with Calcofluor White MR2 fluorescent dye which stains fungal cell walls blue. Pure cultures of Penicillium brevicompactum were used to establish the methods followed by separate experiments with real water biofilm samples in PVC-C and cast iron coupons. FISH demonstrated eukaryotic microrganisms after approximately 5 h while the calcofluor method revealed chitinous and/or cellulose containing filamentous structures in less than one hour. When the two methods were combined, additional resolution was obtained from the images of filamentous walls (blue) with intact protoplasm (red). In conclusion, FISH and Calcofluor staining provide rapid, and direct information on the involvement of filamentous fungi in biofilms which form in water.